PEMBINAAN USAHA BERSAMA KELUARGA SEJAHTERA MELALUI PELATIHAN KEWIRAUSAHAAN DALAM MENINGKATKAN KEMAMPUAN BERWIRAUSAHAN DI KAMPUNG KB PUCANGSAWIT SURAKARTA - Lely firrahmawati; Rina sri widayati; Ayunda Sinta Sumitran; Siti Santika Kusuma Wardani (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Background: The decline in the unemployment rate has an impact on the increase in per capita income and purchasing power of the people, as well as the growth of the national economy. In addition, it also has an impact on reducing the crime rate. Business / entrepreneurship training is a training which can gradually train participants to have entrepreneurial competence and business to train entrepreneurs and businesses. Targets and outputs: entrepreneurship training to improve skills and foster interest and entrepreneurial spirit in the community, gradually train people to have entrepreneurial and business competencies, develop community human resources that can create job opportunities for themselves and others according to development demands, increase family income prosperous village KB Pucang Sawit. The output produced is in the form of handicraft products made of flannel cloth which are transformed into letter recognition materials for children, finger puppets, educational games for kindergarten children. Implementation method: lectures, simulations and demonstrations. Results and Conclusions: Business development activities with prosperous families through entrepreneurship training can improve entrepreneurial skills. In this entrepreneurship training, demonstration methods and skill simulations have been carried out and have produced handicrafts made of flannel cloth in the form of hurricane recognition, finger puppets, shoe stringing.Â